Drinking and haemodynamic changes induced in the dog by intracranial injection of components of the renin-angiotensin system. - Fitzsimons, J T (1978)
1. Intracranial injections of the individual components of the renin-angiotensin system caused drinking in water-replete dogs. 2. Angiotensin II was the most reliable, potent and rapidly acting intracranial dipsogen and elicited drinking in the absence of peripheral circulatory changes. After the highest dose of angiotensin II (10(-9) mole) five dogs drank a mean amount of 380.0 +/- 88.6 ml. For the other components, the order of dipsogenic effectiveness was angiotensin I, synthetic renin substrate, and angiotensin III. 3. Isotonic saline, bradykinin (10(-10) mole), eledosin-hexapeptide (10(-10) mole), oxytocin (10(-10) mole) and prostaglandin F2alpha (1-200 X 10(-12) mole) were ineffective. 4. Intracranial renin (10 m-u.) produced a mean intake of 445 +/- 152 ml. of water in eight dogs. 5. Dog renin substrate and synthetic renin substrate, injected intracranially in a dose of 10(-10) mole, produced similar intakes of water but these amounts were very much less than the volume drunk in response to the same dose of angiotensin II. 6. None of the components injected into dipsogenically responsive sites in the brain caused changes in blood pressure, although the act of drinking itself produced a small rise. 7. Angiotensin II at the highest dose produced drinking when injected into the subfornical organ, preoptic region, anterior hypothalamus, lateral ventricle, third ventricle, ventral hippocampus and mid-line thalamus. Negative sites were found in the caudate nucleus, fourth ventricle, mid-brain, posterior thalamus, dorsal hippocampus, lateral hypothalamus and posterior hypothalamus. 8. After the lowest dose of intracranial angiotensin II (10(-12) mole) only the preoptic region and subfornical orgal were responsive. These two sites were equally sensitive in terms of latency and amounts drunk at all doses injected. 9. Angiotensin did not necessarily have to reach a cerebral ventricle in order to cause drinking. 10. The dog resembles the rat in its responsiveness to the dipsogenic action of intracranial angiotensin II. The regions of the brain from which drinking can be elicited are more widespread than has been claimed by some in the rat.